2010
DOI: 10.1021/ac100921b
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Single Nucleotide Polymorphism Genotyping Utilizing Ligase Detection Reaction Coupled Surface Enhanced Raman Spectroscopy

Abstract: Single nucleotide polymorphisms (SNPs) are one of the key diagnostic markers for genetic disease, cancer progression, and pharmcogenomics. The ligase detection reaction (LDR) is an excellent method to identify SNPs, combining low detection limits and high specificity. We present the first multiplex LDR-surface enhanced Raman spectroscopy (SERS) SNP genotyping scheme. The platform has the advantage in that the diagnostic peaks of Raman are more distinct than fluorescence, and in theory, a clinically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…SERRS is a method with greater resolution than fluorescence, because Raman peaks are sharper. Consequently several SERRS-labeled oligonucleotides can be simultaneously detected if the absorption maxima of the tags are close enough to the laser excitation wavelength [25][26][27][28][29][30]. Maximum absorption of HEX and R6G is at 535 and 524 nm, respectively, and can therefore be simultaneously measured with an argon laser tuned at 514.5 nm [27,29,31,37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SERRS is a method with greater resolution than fluorescence, because Raman peaks are sharper. Consequently several SERRS-labeled oligonucleotides can be simultaneously detected if the absorption maxima of the tags are close enough to the laser excitation wavelength [25][26][27][28][29][30]. Maximum absorption of HEX and R6G is at 535 and 524 nm, respectively, and can therefore be simultaneously measured with an argon laser tuned at 514.5 nm [27,29,31,37].…”
Section: Resultsmentioning
confidence: 99%
“…Several SERRS-labeled oligonucleotides can be simultaneously detected [25][26][27][28][29][30]. A variety of molecules can be detected by SERRS if their absorption maxima are close enough to the laser excitation wavelength.…”
Section: Serrs-labelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,17,21,22] To develop disease diagnostic sensors, it is important to verify that the sensor can identify SNPs in clinical practice. Clinical tests demonstrated that the NW-on-film sensor successfully identified mutations in the relevant DNAs in Avellino corneal dystrophy (ACD) and Wilson disease (WD).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of genetic therapy, clinical diagnosis and molecular biology, SNP is regarded as not only a genetic marker in the study of cancer-related drug metabolism or reactivity, but also a fundamental tool in the identification of inherited disease-causing genes (Imyanitov et al, 2004;McCarthy and Hilfiker, 2000;Sidransky, 2002;Sauna, 2007). Therefore, great efforts have been devoted to developing technique methods for screening SNP, such as allele specific oligonucleotide hybridization (Ding et al, 2010;Liu et al, 2005;Liu and Lin, 2007), endonuclease digestion (Gaylord et al, 2005;Li and Liu, 2009), primer extension (Duan et al, 2009a;Litos et al, 2009;Nelson et al, 1996), oligonucleotide ligation (Huh et al, 2009;Lowe et al, 2010;Xue et al, 2009), nonenzymatic ligation (Xu et al, 2001), DNA-specific redox indicators and conjugated mediators (Drummond et al, 2003;Kelley et al, 1999), in combination with fluorescence (FL) (Duan et al, 2007;Guo et al, 2010;Liu et al, 2009;Wang and Liu, 2007), electrochemistry (Kerman et al, 2004;, chemiluminescence (Liu et al, 2006), colorimetry (He et al, 2010a,b;Lee et al, 2010), and mass spectrometry (Mattes and Seitz, 2001) as signal readout.…”
Section: Introductionmentioning
confidence: 99%